Reproductive biology of the dusky grouper Epinephelus marginatus (Lowe, 1834) - Áthila Bertoncini Andrade; Leonardo Francisco Machado; Maurício Hostim-Silva; João Pedro Barreiros (Brazilian Archives of Biology and Technology, 2003)
Investigations were carried out about the reproductive biology of the dusky grouper, Epinephelus marginatus (Lowe, 1834) a serranid protogynous hermaphrodite fish inhabitant of rocky bottoms from shallow waters up to 200 m depth. Samples were caught in the islands that form Arvoredo Biological Marine Reserve (SC - Brazil) and the coastal islands near Florianópolis region from March 1998 to May 2000. Data from samples of juvenile groupers on intertidal pools were used to link their occurrence in the pools to the post-spawning season. To describe the histological changes on gonads along the reproductive cycle and to establish maturation scales, 109 groupers were histologically tested for sex determination. First maturation size was determined for females (L50=470 mm; r²=0.99). The results of calculated gonadosomatic (GSI) and hepatosomatic (HSI) indexes, showed that maturation occurred along the spring months and the spawning activity during the summer with a peak in December. Liver recovery (HSI elevation) was evident in the autumn, was the post spawning season. The relationship between length and weight was W = 9 · 10-6 · TL3.1149 (r²=0.998; n=246). Este trabalho trata sobre a biologia reprodutiva da garoupa verdadeira, Epinephelus marginatus (Lowe, 1834) um peixe teleósteo pertencente à família Serranidae, hermafrodita protogínico e característico do litoral rochoso, que vive desde águas rasas até os 200 m de profundidade. As amostragens foram realizadas nas ilhas que compõem a Reserva Biológica Marinha do Arvoredo (SC) e ilhas costeiras próximas da região de Florianópolis entre março de 1998 e maio de 2000. Dados de coletas de juvenis em poças de marés foram utilizados visando relacionar a sua ocorrência nestes ambientes com o período de pós-reprodução. Procedeu-se à análise histológica de 109 exemplares, a partir da qual foram descritas as alterações histológicas nas gônadas ao longo do seu ciclo sexual e foram estabelecidas as escalas de maturação. Desta forma determinou-se um tamanho de primeira maturação para as fêmeas (L50=470 mm; r²=0,99). O comportamento dos valores dos índices calculados (Índice Hepatossomático (IHS) e Índice Gonadossomático (IGS)) elucidou um período reprodutivo com maturação das gônadas ao longo dos meses de primavera, vindo a desovar na estação do verão, sendo nítida a recuperação do fígado (elevação do IHS) no outono, pós reprodução. Calculou-se também a relação peso comprimento P = 9 · 10-6 · CT 3,1149 (r²=0,998; n=246).